Measuring spin and CP from semihadronic ZZ decays using jet substructure - Englert, Christoph; Hackstein, Christoph; Spannowsky, Michael (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We apply novel jet techniques to investigate the spin and CP quantum numbers of a heavy resonance X, singly produced in pp→X→ZZ→ℓ+ℓ−jj at the LHC. We take into account all dominant background processes to show that this channel, which has been considered unobservable until now, can qualify under realistic conditions to supplement measurements of the purely leptonic decay channels X→ZZ→4ℓ. We perform a detailed investigation of spin- and CP-sensitive angular observables on the fully simulated final state for various spin and CP quantum numbers of the state X, tracing how potential sensitivity communicates through all the steps of a subjet analysis. This allows us to elaborate on the prospects and limitations of performing such measurements with the semihadronic final state. We find our analysis particularly sensitive to a CP-even or CP-odd scalar resonance, while, for tensorial and vectorial resonances, discriminative features are diminished in the boosted kinematical regime.